Content assessment of the primary biodiversity data published through GBIF network: Status, challenges and potentials - Gaiji, Samy; Chavan, Vishwas; Ariño, Arturo H.; Otegui, Javier; Hobern, Donald; Sood, Rajesh; Robles, Estrella (Biodiversity Informatics, 2013)
With the establishment of the Global Biodiversity Information Facility (GBIF) in 2001 as an inter-governmental co-ordinating body, concerted efforts were made during the past decade to establish a global research infrastructure to facilitate the sharing, discovery and access to primary biodiversity data. As on date the participants in GBIF have enabled the discovery and access to over 267+ million such data records. While this remarkable achievement in terms of volume of data must be acknowledged, concerns about the quality and ‘fitness-for-use’ of the data should also be carefully considered in future developments. This contribution is therefore a direct response to the calls for comprehensive content assessment of the GBIF mobilised data. It is the first comprehensive assessment of the coverage of the content mobilised so far through GBIF, as well as a mean to identify the existing gaps and reflect on fitness-for-use requirements. This paper describes the complementary methodologies adopted by the GBIF Secretariat and University of Navarra for the development of a comprehensive content assessment. Outcomes of these research initiatives are summarised in four categories, namely, (a) data quality assessment, (b) trends/patterns assessment, (c) fitness-for-use assessment, and (d) ecosystem specific data diversity assessment. In conclusion we make specific suggestions to the GBIF community on the adoption of common indicators to assess progress towards future targets as well as recommendations to populate such exercise at various levels within the GBIF Network from national level to thematic levels.